Analysis of Permeability Coefficient on Stabilished Peat using Bacillus Subtilis Bacteria - Annisa Khoerani; dewi amalia; Suherman Sulaiman (Potensi: Jurnal Sipil Politeknik, 2024)
In construction sector, peat is one type of soil that is avoided because it has poor characteristics. This is because peat has very different characteristics when compared to other types of soil. Poor peat characteristics often lead to damage and construction failure of infrastructure buildings on peat. For example, large settlement values are caused by high peat compression that strongly influenced by its permeability value. The smaller the permeability value, the smaller the compression that occurs. Indonesia has the largest peatland distribution in Southeast Asia, this is a problem that must be resolved immediately. Much research has been done to improve the characteristics of peat, one of which is peat stabilization. Microbially Induced Calcite Precipitation (MICP) method using Bacillus subtilis was considered as an effective method in peat stabilization. This stabilization can reduce the permeability value of the peat by closing the pores in the peat. To investigate the influence of the bacteria on the peat sample, several tests was conducted including the physical property and permeability test. In this study, the addition of Bacillus subtilis bacteria solution can reduce the permeability value of peat from 0.001170 cm/sec to 0.000317 cm/s at the addition of 5% bacteria solution.